Vie et miracles de Daniel de Qorqor. Traduction française - Gérard Colin (Afriques)
This edition and translation of the Life and Miracles of Daniel is based on a manuscript still kept in the church of Māryām Qorqor. Covered with wooden boards, it measures 34.5 x 30 x 9 cm and has 115 folios of parchment. It was completed in the year 1968 of the Ethiopian era (AD 1975-1976. J.-C.).